Factors related to anatomical and functional success of rhegmatogenous retinal detachment surgery at the Regional Institute of Ophthalmology "Javier Servat Univazo" (2010 – 2019), Trujillo, Peru - Quezada-Osoria, Marita Lucía (2023)
Objective: To determine the factors related to the anatomical and functional success of surgery for rhegmatogenous retinal detachment (RRA) in patients of the Regional Institute of Ophthalmology "Javier Servat Univazo".  Materials and methods: retrospective observational cohort study of 204 patients with RRD submitted to different surgical techniques between January 2010-December 2019, with at least 6 months of follow-up.  The variables studied were: anatomical success (primary retinal reapplication) and functional success (improvement in visual acuity [VA]); looking for an association between these variables and demographics, clinics and waiting times. Results: The mean age was 50 + 16.5 (9-85) years. Anatomical success was achieved in 165 (80.9%) patients and functional in 110 (52.9%). There was a shorter surgical waiting time in patients who achieved anatomical success (20.0 +/- 22.6 days [1-120]) vs (29.8 +/- 40.1 days [1-210]) (p=0.04) and in those who had functional success (13.3+/- 15.1 [1-100]) vs (31.9 +/- 33.7 [1-210]) (p=0.0002); and shorter sick time and shorter total time in those who had functional success (29.7 +/-56.5 days [1-365] vs (61.9 +/- 110.6 days [1-730]) (p = 0.008) and (43.1 +/-68.1 [5-465]) vs 93.8 +/- 118.3 [3-766]) respectively (p = 0.0002). Conclusions: The shorter surgical waiting time was associated with RRD surgery's anatomical and functional success. The shortest time of illness and the shortest total time were associated with functional success. We recommend implementing measures to shorten waiting times and establish early and timely surgical therapy in these patients.